2019
DOI: 10.3390/cancers12010061
|View full text |Cite
|
Sign up to set email alerts
|

ERK Activation Modulates Cancer Stemness and Motility of a Novel Mouse Oral Squamous Cell Carcinoma Cell Line

Abstract: We established the NHRI-HN1 cell line from a mouse tongue tumor induced by 4-nitroquinoline 1-oxide (4-NQO)/arecoline, with further selection for cell stemness via in vitro sphere culture, to evaluate potential immunotherapies for oral squamous cell carcinoma (OSCC) in East and Southeast Asia. In vivo and in vitro phenotypic characterization, including tumor growth, immune modulator administration, gene expression, morphology, migration, invasion, and sphere formation assays, were conducted. NHRI-HN1 cells are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…This is the only cell line that has been developed from a spontaneous tumor without exposure to any carcinogen. Normally, murine OSCC cell lines are either p53 mutant cell lines or p53 wild type cell lines [ 2 , 7 , 8 , 9 ]. However, MPC-1 is a p53 null cell line.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is the only cell line that has been developed from a spontaneous tumor without exposure to any carcinogen. Normally, murine OSCC cell lines are either p53 mutant cell lines or p53 wild type cell lines [ 2 , 7 , 8 , 9 ]. However, MPC-1 is a p53 null cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies on human OSCC cell lines have allowed there to be remarkable research progress and an identification of new interventions, the immune-compromised preclinical platforms developed from these tumorigenic cell lines are not suitable for addressing questions related to the immune responses that target tumor growth [ 5 , 6 ]. Therefore, murine OSCC cell lines have been developed in the past few years in order to generate immune-competent preclinical models that can be used to assess tumor targeting [ 2 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Srivastava et al [ 10 ] showed FAT1 gene, an ortholog of Drosophila tumor suppressor gene fat, modulates EMT and stemness genes expression in hypoxic glioblastoma. ERK was also found to suppress oral squamous carcinoma cell migration and reduce stemness characteristics [ 11 ]. Although hyperproliferative capacity and overproduction of gastric tumor cells are likely closely related to EMT and tumor stemness [ 12 , 13 ], data about identification of molecular markers pertinent to pathogenic process and potential therapy are largely lacking.…”
Section: Introductionmentioning
confidence: 99%